EXTUBATION FAILURE NEONATAL VERY LOW BIRTH WEIGHT IN NEONATAL INTENSIVE CARE OF A MEDIUM-SIZED CITY (Fiep Bulletin - online, 2012)
Advances in neonatal medicine has provided a significant increase in survival of newborns. Invasive mechanical ventilation is a key feature for these newborns, but it has contributed to the aggravation of pulmonary lesions, increasing morbimortatidade in premature newborns. The discontinuation of mechanical ventilation should be sought as soon as possible in order to minimize potential damage, and indicators used to evaluate lung mechanics, gas exchange and respiratory muscle strength, but no index is sensitive and specific enough to be predictive. This study aimed to determine the prevalence of extubation failure in infants of very low birth weight, neonatal ICU care center in western regions, and to evaluate the parameters for extubation in these newborns. Most patients (57.9%) had a diagnosis of prematurity. Among the 202 newborns, 25 newborns were very low birth weight, however due to exclusion criteria, data were considered only 8 cases. The mean (± SD) of mechanical ventilation in the study group was 123.5 ± 109.8 hours, during hospitalization. Three newborn very low birth weight had extubation failure, requiring new support invasive.
Keywords: Neonatal intensive care unit; Mechanical Ventilation; Extubation.